Intraoperative Thrombophilia-Associated Thrombosis of Both Saphenous Veins during Harvesting for Coronary Artery Bypass Grafting - Mazur, Piotr; Ząbczyk, Michał; Litwinowicz, Radosław; Natorska, Joanna; Kapelak, Bogusław (TH Open, 2020)
Introduction Intraoperative thrombosis of saphenous veins (SV) during open harvesting is very rare.Case Report We present a case of a 60-year-old male patient with multivessel coronary artery disease and a history of a non-ST elevation acute coronary syndrome, and type-2 diabetes mellitus admitted for coronary artery bypass grafting, in whom bilateral intraoperative SV thrombosis occurred during graft harvesting. Routine thrombophilia screening showed no abnormalities and cancer was excluded. Compared with healthy controls, we observed prolonged fibrin clot lysis time and increased thrombin generation reflected by endogenous thrombin potential. Scanning electron microscopy of the thrombosed material revealed compact and thick fibrin layer on the clot surface with a solid mass of unusually compressed platelets and erythrocytes underneath. The patient was tested for fibrinogen and factor (F) XIII polymorphisms, and was found to be heterozygous for β-fibrinogen HaeIII (-455G > A) and FXIII Val34Leu (100G > T).Conclusion β-fibrinogen HaeIII and FXIII Val34Leu polymorphisms are reflected in reduced clot permeability and susceptibility to lysis, and might contribute to intraoperative SV thrombosis during vascular grafting procedures. Carriers of those are at risk of primary venous graft failure after bypass procedures.
Keywords: coronary artery bypass grafting; thrombosis; fibrin; fibrinogen; mutation